ANALYSIS OF THE EFFECTIVENESS OF GOVERNMENT ASSISTANCE FOR MICRO BUSINESS (BPUM) IN THE VILLAGE MANGUNEGARA, MREBET DISTRICT, PURBALINGGA DISTRICT - Miftahul Nurul Huda; Taufik Purboyo; Emilius Gudonohadi (DYNAMICS: Journal of Public Administration, 2023)
This research is entitled "Analysis of the Effectiveness of Micro Business Government Assistance (BPUM) in Mangunegara Village, Mrebet District, PurbalinggaRegency". The purpose of this study was to describe and explain the effectiveness of government assistance for micro-enterprises in Mangunegara village, Mrebet sub-district,Purbalingga district. This research method is descriptive and qualitative. Informants were determined by purpose sampling method. The analysis of research results using an interactive analysis model. Based on the results of the study, several conclusions can be drawn as follows (1). Productivity Aspect, Strategy to market the products by promoting them through social media, with close friends, and family. The results from the sale have not been in line with expectations because they have not reached the target quality. Sometimes sales are at a loss; (2) Aspects of quality, the price of products on the market is not too cheap or too expensive, so there is no price competition with other entrepreneurs. The quality of the products of business actors can easily add selling value to damaged products; (3). Aspects of Efficiency, Entrepreneurs in managing finances, separating Personal and Corporate Finances, making Financial Books, determining FinancialPortions, how to overcome existing losses by promoting more often on social media so that more people are interested in buying, evaluating, improving business systems,making changes ; (4). Aspects of Flexibility, how to deal with competitors who also have similar businesses by improving product quality so that they are not less competitive with those on the market and continue to innovate to make it easier to maintain loyalty to customers. Changes that occur in an organization suggest employees think carefully about their decisions, conduct evaluations, conducting recruitment; (5). Satisfaction Aspect,there are 5 to 10 variants made for sale, how to deal with consumer complaints by receiving complaints properly, good communication on complaints and immediately handling Complaints quickly and providing the Best Solutions; (6). Aspects of Excellence. innovation made to keep this business afloat by adding various variants of forms to keep this business afloat are in the form of a solid work team, prioritizing customer desires,making quality products following the times and maximizing the use of technology.